Preparation of Palm Oil Mill Effluent Sludge Biochar for the Treatment of Landfill Leachate - Bashir, M.J.K. (EDP Sciences, 2017)
In recent years, landfilling has emerged as the most widely employed method for municipal solid waste disposal especially in ASEAN countries. However, due to the presence of refractory compounds in stabilized landfill leachates which results in the inefficiency of biological treatment methods, other alternatives such as physico-chemical treatment methods are being look into and adsorption method seems promising. Nevertheless, the raw materials used for the preparation of adsorbents in the industry are usually non-renewable materials thus resulting in high operational costs. Therefore, present study evaluates the ability of palm oil mill effluent sludge (POMES) derived biochar in the treatment of chemical oxygen demand (COD), color and ammoniacal nitrogen (NH3-N) from stabilized landfill leachate obtained from Sahom landfill located in Kampar, Perak, Malaysia using response surface methodology (RSM) technique. It was found that the removal efficiency of the leachate pollutants by POMES biochar is highly dependent on the production process such as temperature and holding time. In this study, 44.26 of COD, 70.20 of color and 30.56 of NH3-N were removed from stabilized landfill leachate via optimized biocharat452°C temperature and 66 minutes of holding time. © The Authors, published by EDP Sciences, 2017.